Dresden PTSD treatment study: randomized controlled trial of motor vehicle accident survivors - Maercker, Andreas (BioMed Central, 2006)
BACKGROUND: We translated, modified, and extended a cognitive behavioral treatment (CBT) protocol by Blanchard and Hickling (2003) for the purpose of treating survivors of MVA with full or subsyndromal posttraumatic stress disorder (PTSD) whose native language is German. The treatment manual included some additional elements, e. g. cognitive procedures, imaginal reliving, and facilitating of posttraumatic growth. The current study was conducted in order to test the efficacy of the modified manual by administering randomized controlled trial in which a CBT was compared to a wait-list control condition. METHODS: Forty-two motor vehicle accident survivors with chronic or severe subsyndromal posttraumatic stress disorder (PTSD) completed the treatment trial with two or three detailed assessments (pre, post, and 3-month follow-up). RESULTS: CAPS-scores showed significantly greater improvement in the CBT condition as compared to the wait list condition (group × time interaction effect size d = 1.61). Intent-to-treat analysis supported the outcome (d = 1.34). Categorical diagnostic data indicated clinical recovery of 67% (post-treatment) and 76% (3 months FU) in the treatment group. Additionally, patients of the CBT condition showed significantly greater reductions in co-morbid major depression than the control condition. At follow-up the improvements were stable in the active treatment condition. CONCLUSION: The degree of improvement in our treatment group was comparable to that in previously reported treatment trials of PTSD with cognitive behavioral therapy. TRIAL REGISTRATION: ISRCTN66456536